Listen up Philip [videorecording (DVD)] - Perry, Alex Ross; Schwartzman, Jason, 1980-; Moss, Elisabeth, 1982-; Pryce, Jonathan (Tribeca Film, 2014)
Anger rages in Philip as he awaits the publication of his second novel. He feels pushed out of his adopted home city by the constant crowds and noise, a deteriorating relationship with his photographer girlfriend Ashley, and his own indifference to promoting the novel. When Philip's idol Ike Zimmerman offers his isolated summer home as a refuge, he finally gets the peace and quiet to focus on his favorite subject: himself.